2019
DOI: 10.1371/journal.pone.0213974
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating weight-restored anorexia nervosa and body dysmorphic disorder using neuroimaging and psychometric markers

Abstract: Anorexia nervosa (AN) and body dysmorphic disorder (BDD) are potentially life-threatening conditions whose partially overlapping phenomenology—distorted perception of appearance, obsessions/compulsions, and limited insight—can make diagnostic distinction difficult in some cases. Accurate diagnosis is crucial, as the effective treatments for AN and BDD differ. To improve diagnostic accuracy and clarify the contributions of each of the multiple underlying factors, we developed a two-stage machine learning model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Finally, to our knowledge, although investigators have separately tested neurofunctional or psychometric classifiers (e.g., self‐reported measures that predict the onset of bipolar disorder in adolescents 136,137 ), no studies have yet combined these classifiers in bipolar depression. Combining psychometric and neurofunctional classifiers in other mental health conditions has been shown to increase the accuracy of classification 138‐140 . It would also be useful to investigate how neurofunctional classifiers improve diagnostic accuracy in addition to standard clinical diagnostic metrics 4,132,141 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to our knowledge, although investigators have separately tested neurofunctional or psychometric classifiers (e.g., self‐reported measures that predict the onset of bipolar disorder in adolescents 136,137 ), no studies have yet combined these classifiers in bipolar depression. Combining psychometric and neurofunctional classifiers in other mental health conditions has been shown to increase the accuracy of classification 138‐140 . It would also be useful to investigate how neurofunctional classifiers improve diagnostic accuracy in addition to standard clinical diagnostic metrics 4,132,141 …”
Section: Discussionmentioning
confidence: 99%
“…Combining psychometric and neurofunctional classifiers in other mental health conditions has been shown to increase the accuracy of classification. [138][139][140] It would also be useful to investigate how neurofunctional classifiers improve diagnostic accuracy in addition to standard clinical diagnostic metrics. 4,132,141 Studies included in this review applied well-validated and standardized mood disorder diagnostic measures, but clinical measures are ultimately subjective.…”
Section: Future Directionsmentioning
confidence: 99%
“…In HC, this community comprised the right caudate, right accumbens, right ACC, right posterior cingulate, and right pallidum, while in AN-wr it included the right caudate, right accumbens, right rostral ACC, right medial and lateral OFC, and right frontal pole (the BDD-a module shared some elements with each of other groups, see Table 2 for details). Based on these results, the second study [ 26 ] implemented a two-step machine learning model using DTI-based NPL as a feature in conjunction with other measures (i.e. task-related FC, anxiety, depression, and insight).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, (Serino et al, 2016) and colleagues showed that with immersive virtual reality is possible to modify the body memory in AN. Again, the combined use of neuroscientific measures and innovative methods like ML can be useful for diagnosis and prognosis of this complex psychiatric disorder (Haynos et al, 2020;Lavagnino et al, 2018;Vaughn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%